Chemisorption of methanol on different platinum electrodes (smooth and rough polycrystalline, monocrystalline, and preferentially oriented), as studied by EMIRS - Beden, B. (1989)
EMIR spectra of methanol electroadsorbates on smooth and rough polycrystalline, monocrystalline and preferentially oriented platinum electrodes are reported. The (100)-type preferred oriented platinum behaves approximately as Pt (100) single crystals. On electrodispersed platinum electrodes the poisoning phenomena due to CO adsorbates appear to be reduced as compared to smooth platinum electrodes. EMIRS results correlate well with the electrochemical behaviour of the different platinum electrodes for methanol electrooxidation.